2018
DOI: 10.3897/compcytogen.v12i1.21799
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic reconstruction and localization of the (TTAGG)n telomeric repeats in the chromosomes of Acromyrmex striatus (Roger, 1863) suggests a lower ancestral karyotype for leafcutter ants (Hymenoptera)

Abstract: Chromosome counts and karyotype characterization have proved to be important features of a genome. Chromosome changes during the diversification of ants might play an important role, given the diversity and success of Formicidae. Comparative karyotype analyses on ants have enriched and helped ant systematics. Among leafcutter ants, two major chromosome counts have been described, one frequent in Atta Fabricius, 1804 (2n = 22 in all Atta spp. whose karyotype is known) and the other frequent in Acromyrmex Mayr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…Similar distribution patterns have also been observed in Citrus species (Deng et al, 2019); Berberis species (Liu and Luo, 2019); and Fraxinus, Syringa, and Ligustrum species (Luo and Liu, 2019a). FISH probes (AG 3 T 3 ) 3 located at chromosome ends ensure accurate chromosome counts (Pereira et al, 2018), although (AG 3 T 3 ) 3 is also occasionally observed in the internal positions of chromosomes (Murray et al, 2002;Majerová et al, 2014;Vasconcelos et al, 2018). Because 5S rDNA and (AG 3 T 3 ) 3 were inadequate for identifying the Sichuan walnut cultivars, it was necessary to perform further detection.…”
Section: Distinguishing Sichuan Walnut Cultivars By Molecular Cellulasupporting
confidence: 63%
See 1 more Smart Citation
“…Similar distribution patterns have also been observed in Citrus species (Deng et al, 2019); Berberis species (Liu and Luo, 2019); and Fraxinus, Syringa, and Ligustrum species (Luo and Liu, 2019a). FISH probes (AG 3 T 3 ) 3 located at chromosome ends ensure accurate chromosome counts (Pereira et al, 2018), although (AG 3 T 3 ) 3 is also occasionally observed in the internal positions of chromosomes (Murray et al, 2002;Majerová et al, 2014;Vasconcelos et al, 2018). Because 5S rDNA and (AG 3 T 3 ) 3 were inadequate for identifying the Sichuan walnut cultivars, it was necessary to perform further detection.…”
Section: Distinguishing Sichuan Walnut Cultivars By Molecular Cellulasupporting
confidence: 63%
“…Fluorescence in situ hybridization (FISH) with probe-labeled chromosome ends enables accurate counting of small walnut chromosomes (Deng et al, 2019;Liu and Luo, 2019;Luo and Liu, 2019a). Karyotype analysis aids in chromosome physical map construction and chromosome assembly (Hizume et al, 2002;Luo et al, 2017;Luo et al, 2018;Pereira et al, 2018), thereby providing a guide for distinguishing Sichuan walnut cultivars to a certain degree. However, no walnut cultivars have been subjected to FISH analysis.…”
Section: Introductionmentioning
confidence: 99%
“…() dated the last common ancestor of these two clades to, respectively, 25 mya (range: 11–39 mya) and 22.4 mya (16.9–27.9 mya), suggesting that Clade‐A fungi may have originated before the origin of leafcutter fungiculture (see Mueller et al., for further discussion). The cultivation of a Clade‐B fungus by Acromyrmex striatus (Figure ), the most basal (earliest‐diverging) lineage in the leafcutter clade (Cristiano et al., ; Branstetter et al., ; Pereira, Reis, Cardoso, & Cristiano, ), would support a possible ancestral leafcutter fungiculture that included Clade‐B fungi. However, the cultivation of a mix of Clade‐A and Clade‐B fungi by species in the leafcutter clade and especially in the septentrionalis ‐clade of Trachymyrmex (sister clade to the leafcutter ant clade; Rabeling, Cover, Johnson, & Mueller, ; Schultz & Brady, ; Schultz et al., ) suggests the possibility of a mix of Clade‐A and Clade‐B cultivation that preceded the origin (most recent common ancestor) of leafcutter ants and the septentrionalis ‐clade.…”
Section: Resultsmentioning
confidence: 95%
“…Specifically, the (TTAGG) n motif was initially considered characteristic of this order in general (Frydrychová et al, 2004). However, at that time this motif was detected only on chromosomes of certain aculeate Hymenoptera, i.e., the honeybee, Apis mellifera Linnaeus, 1758, from the family Apidae as well as about 20 ant species (Formicidae), using either FISH or SBH (Lorite, Carrillo, & Palomeque, 2002;Meyne & Imai, 1995; see also Korandová et al, 2014;Okazaki et al, 1993;Pereira, dos Reis, Cardoso, & Cristiano, 2018;Wurm et al, 2011). Interestingly, the telomeres of A. mellifera appeared to be a mosaic of short TTAGG repeats interspersed with TCAGGCTGGG, TCAGGCTGGGTTGGG, and TCAGGCTGGGTGAGGATGGG higher order repeat arrays (Garavís et al, 2013).…”
Section: Coleoptera (Beetles)mentioning
confidence: 99%